TAKING THE TOOL ANALOGY SERIOUSLY: FORMS AND NAMING IN THE CRATYLUS. (12th May 2014) - Smith, Imogen
Abstract : It has been suggested that the so-called tool analogy passage of Plato's Cratylus presents us with a moderate linguistic naturalism that can stand or fall independently of the more unpalatable etymological and mimetic theories advanced later in the dialogue. This paper offers a reading of the tool analogy which argues that Socrates' employment of Forms (and in particular Species-Forms), together with a careful distinction between the types of knowledge associated with making and using tools, aims to establish a radical linguistic naturalism that constrains the intrinsic properties of names. This should be clear if we take Socrates' claim seriously that names are tools: tools in general can only function successfully if they exhibit the relevant structural, compositional and (to some extent) material properties. Since Socrates claims that names are a class of tools and not merely like tools in some respects, as many have supposed, then what holds for tools in general must also hold for names.